2019
DOI: 10.1177/0022167819847328
|View full text |Cite
|
Sign up to set email alerts
|

Why Women Veterans Do Not Use VA-Provided Health and Social Services: Implications for Health Care Design and Delivery

Abstract: Background: The Veterans Administration (VA) is transforming its historically male-dominated health care system to better serve women veterans, few of whom, nevertheless, use VA health care. We describe the factors affecting women veterans' use of VA-provided health care. Methods: We conducted in-person interviews with 22 women veterans in Los Angeles, California, from 2013 to 2015 who received some non-VA health care. Using grounded theory, we inductively identified the major themes and selected illustrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…This study confirms barriers to healthcare access identified in recent studies of rural and veterans' healthcare (e.g., Author; CAMH 2015; Evans et al 2019; NCVAS 2015; 2017; Sanders et al 2015). For example, our findings support the need for more information about the VA health services, particularly among older, rural women veterans who need to establish eligibility for VA services.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This study confirms barriers to healthcare access identified in recent studies of rural and veterans' healthcare (e.g., Author; CAMH 2015; Evans et al 2019; NCVAS 2015; 2017; Sanders et al 2015). For example, our findings support the need for more information about the VA health services, particularly among older, rural women veterans who need to establish eligibility for VA services.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, an important limitation to this study concerns its generalizability. Specifically, while this case study supports the findings of Evans et al (2019) for urban women veterans and their recommendations to address persistent barriers, the relevance of our findings to veterans in other rural and urban locations cannot be addressed with these case study data. To this end, additional research is needed that allows for a comparison of veterans' experiences in other locales that would help assess the applicability of our findings in different contexts and identify other contextual barriers.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations